2012
DOI: 10.1016/j.technovation.2011.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Rejuvenating clusters with ‘sleeping anchors’: The case of nanoclusters

Abstract: This article investigates how anchor firms sustain high tech clusters rejuvenation by means of technological pre-adaptation. Based on evidences are drawn from the comparison of the evolution of two nano-electronics clusters, i.e., Grenoble (France) and Catania (Italy) clusters which are sharing the same anchor tenant firm STMicroelectronics. Cluster rejuvenation comes from pre-adaptation of actors (scientific and technological diversity), competition amongst anchor tenant firms, competition and overlap amongst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 55 publications
1
38
0
1
Order By: Relevance
“…Geographical proximity generates also other benefits for co-located actors because these hubs create economies of scale in services such as infrastructure and specialized labor. While previous empirical work found that the anchor role can be played by a large, incumbent high-tech firm (Baglieri and Cinici Mangematin, 2012) or a university (Feldman, 2003), our findings complements previous evidence by adding that private-public research centers can accelerate anchor model benefits, stimulating both the demand and supply sides of local markets for innovation, and efficiently channeling and orchestrating knowledge spillovers. Contrasting this experience, the Japanese nanotech knowledge production is widely dispersed among a huge number of large, incumbent firms, and reveals a different strategy that Japan is pursuing, that is, a deliberate movement away from a "anchor-tenant model" in favor of a higher actor variety, with the aim to leverage firms' alliance portfolios and access external patents.…”
Section: Discussionsupporting
confidence: 83%
“…Geographical proximity generates also other benefits for co-located actors because these hubs create economies of scale in services such as infrastructure and specialized labor. While previous empirical work found that the anchor role can be played by a large, incumbent high-tech firm (Baglieri and Cinici Mangematin, 2012) or a university (Feldman, 2003), our findings complements previous evidence by adding that private-public research centers can accelerate anchor model benefits, stimulating both the demand and supply sides of local markets for innovation, and efficiently channeling and orchestrating knowledge spillovers. Contrasting this experience, the Japanese nanotech knowledge production is widely dispersed among a huge number of large, incumbent firms, and reveals a different strategy that Japan is pursuing, that is, a deliberate movement away from a "anchor-tenant model" in favor of a higher actor variety, with the aim to leverage firms' alliance portfolios and access external patents.…”
Section: Discussionsupporting
confidence: 83%
“…establishing common language portfolios in relation to KOs between OM and AS actors using the KOs of lean PMs and Lean Value Streams) and semantic knowledge sharing (developing shared meanings for insipient KOs) with relatively high levels of "amplified uncertainty" (Baglieri et al, 2012). The Lean KOs are seen as becoming more defined at the project progresses with jointly agreed Lean PM sets and Lean Value Streams being established and readily transferable amongst all of the actors involved (Letti et al, 2008).…”
Section: Mcgivern and Dopsonmentioning
confidence: 99%
“…Three of the member organisations that act as so-called anchor tenants were included in the selection (see Baglieri et al, 2012). This set of criteria sought to prevent a bias in the findings.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…This may result in a negative lock-in that hinders cluster change as the cluster is too socially embedded (Engstrand and Stam, 2002). Finally, anchor tenants that play a key role in coordinating partnerships and setting up new initiatives may resist change in fear of upcoming rivals taking their positions (see Baglieri et al, 2012). This scenario could be even more problematic given the uneven distribution of power.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
See 1 more Smart Citation